Perspektif Buddhis Tentang Makanan: Memahami Konsep Halal Dan Haram - Medhacitto, Tri Saputra; Sukodoyo; Suranto (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
The research examines the Buddhist perspective on food consumption, by exploring the understanding of the concepts of halal and haram in Buddhism. This research was conducted using a literature study approach, by examining Buddhist scriptures and relevant literature such as books, journals, scientific articles, to compare the Buddhist perspective on eating etiquette with the concepts of halal and haram in Islam. The findings show that halal and haram refer to foods that are and are not allowed to be consumed. Although Buddhism does not have specific terms similar to halal and haram, Buddhism has a set of moral and ethical principles that have the same function as the concepts of halal and haram, which guide humanity to determine what is permissible and what is not. Buddhism has the term "bhojana Sappāya" or "supportive food" which can be understood as a food that is suitable for the body, can improve the health of the body, is easy to eat and digest. In principle, Buddhism views the good and bad of a food not only in terms of the content in it, but also includes the way it is eaten and the way it is obtained. Eating should be obtained in a way that does not violate Buddhist morality. Meats that should not be consumed are human flesh (manussamaṃsaṃ), elephants (hatthimaṃsaṃ), horses (assamaṃsaṃ), dogs (sunakhamaṃsaṃ), snakes (ahimaṃsaṃ), lions (sīhamaṃsaṃ), tigers (byagghamaṃsaṃ), leopards (dīpimaṃsaṃ), bears (acchamaṃsaṃ), and hyenas (taracchamaṃsaṃ). Etiquette when it comes to eating has been set out in sekhiyavatta, which allows one to have a polite and respectful way of eating.